Dry powder inhaler of colistimethate sodium for lung infections in cystic fibrosis: optimization of powder construction. (3rd October 2019) - Kozáková, Jana; Altay, Ayça; Ždímal, Vladimír; Mašková, Ludmila; Sonvico, Fabio; Quarta, Eride; Rossi, Alessandra; Buttini, Francesca; Colombo, Gaia
Abstract: Colistimethate sodium (CMS) for treatment of lung infections in cystic fibrosis patient was transformed into a dry powder for inhalation by spray drying. Design of Experiment was applied for understanding the role of the spray-drying process parameters on the critical quality attributes of the CMS spray-dried (SD) powders and agglomerates thereof. Eleven experimental SD microparticle powders were constructed under different process conditions according to a central composite design. The SD microparticles were then agglomerated in soft pellets. Eleven physico-chemical characteristics of SD CMS microparticle powders or agglomerates thereof were selected as critical quality attributes. The yield of SD process was higher than 75%. The emitted fraction of agglomerates from RS01 inhaler was 75–84%, and the fine particle fraction (particles <5 µm) was between 58% and 62%. The quality attributes of CMS SD powders and respective agglomerates that were significantly influenced by spray-drying process parameters were residual solvent and drug content of the SD microparticles as well as bulk density and respirable dose of the agglomerates. These attributes were also affected by the combination of the process variables. The air aspiration rate was found as the most positively influential on drug and solvent content and respirable dose. The residual solvent content significantly influenced the powder bulk properties and aerodynamic behavior of the agglomerates, i.e. quality attributes that govern drug metering in the device and the particles lungs deposition. Agglomerates of CMS SD microparticles, in combination with RS01 DPI, showed satisfactory results in terms of dose emitted and fine particle fraction.